STRATEGI PENINGKATAN DAYA SAING LADA PUTIH INDONESIA MELALUI ANALISIS PENAWARAN EKSPOR DAN PERMINTAAN IMPOR LADA PUTIH DUNIA - -, EDIZAL (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
This study is competitive increasing strategy of Indonesian white pepper (muntok white pepper). The main objective of this study are : 1) The analysis supply for export white pepper from Indonesia, Malaysia, Brazil and Singapore; 2) The analysis demand for import white pepper by United State of America, European Economy Community, Japan, Singapore and ROW. The results of supply export white pepper from Indonesia, Malaysia, Brazil and Singapore in the short run is inelastic. In the long run supply export white pepper from Indonesia, Malaysia, and Brazil is elastic, meanwhile Singapore is inelastic. The result of demand for import white pepper by United State of America, European Economy Community, and Japan an ROW in the short run is inelastic, meanwhile Singapore is elastic.
Keywords: White Pepper, Supply for Export, Demand for Import, Elasticity